Enhancing vocational students’ mathematical problem-solving through contextual teaching factory learning - Muhtarom Muhtarom; Hary Nurprio Utomo; Ida Dwijayanti (Universitas Hamzanwadi, 2026)
The discrepancy between classroom mathematics and the demands of the Business and Industrial World often results in less-than-ideal problem-solving ability for vocational high school students. To meet this challenge, learning methods that link mathematics to real-world work contexts are needed. The purpose of this study is to investigate the effectiveness of integrating the Teaching Factory (TeFa) model with a contextual learning approach in teaching relations and functions. A quantitative quasi-experimental method with the pre-test–post-test control group design was employed. The sample was 46 eleventh-grade pharmacy students at Muhammadiyah Al Manaar Vocational High School, Pemalang, selected through purposive sampling and divided equally into experimental and control groups. Data were collected using a validated mathematical problem-solving instrument and analysed using an independent samples t-test. Post-test performances differed significantly between the two groups (p < 0.05). The experimental group gained a moderate improvement with an N-gain score of 0.42. Moreover, the Cohen’s d value of 0.81 indicated a large effect of the TeFa model compared with conventional instruction. These findings indicate that the integration of TeFa and contextual learning is effective to improve students’ mathematical problem-solving abilities while reinforcing the relevance of mathematics learning to real industrial workplace contexts in vocational education.